A Homogeneous‐Heterogeneous Kinetic Study of Oxidative Coupling of Methane (OCM) on La2O3/CeO2 Catalyst. Issue 23 (26th October 2022) - Wang, Haoyi; Yang, Chaobo; Shao, Can; Alturkistani, Sultan; Magnotti, Gaetano; Gascon, Jorge; Takanabe, Kazuhiro; Sarathy, S. Mani
Abstract: A La2 O3 /CeO2 catalyst was synthesized and achieved 19 % C2+ yield with 65 % C2+ selectivity at 650 °C. The doping of CeO2 not only enhanced catalytic performance, but also improved catalyst stability in the presence CO2 and H2 O. This study investigated the kinetics on La2 O3 /CeO2 over a wide range of operating conditions. Planar laser‐induced fluorescence was implemented to directly observe the presence of formaldehyde, as the first time reported in OCM. A packed bed reactor model was constructed based on the dimensions of experimental setup and catalyst characterization. Rather than using a tuned gas phase model, the experimentally validated mechanism NUIGMech1.1 was implemented. The proposed homogeneous‐heterogeneous OCM mechanism kinetic model was validated against experimental data under isothermal conditions, and the results show good agreement with measured species. The rate of production (ROP) was performed to identify the important reactions and prove the necessity of surface reactions for the OCM process. Abstract : The doping of CeO2 enhanced catalytic performance and improved catalyst stability over La2 O3 catalyst. A proposed kinetic mechanism was validated against experimental data under isothermal conditions in good agreement with measured species. Planar laser‐induced fluorescence was implemented to directly observe the presence of formaldehyde, which indirectly demonstrates the feasibility of the proposed model and reaction network.